GAME-DESIGN MODEL FOR CULTURALLY -ENHANCED SERIOUS GAME - MOHO ARIFFIN, MAZEYANTI (2015)
Young learners have different learning expectations and learning styles as compared to previous generation of learners. Extensive exposure to technologies makes them anticipates active roles. immediate feedbacks. interactions, experiential learning and expect associations between content and real-life situations from their learning environment. However. the current teaching deliveries lack on these elements. Besides these aspects. studies also revealed that utilizing Ieamer"s cultural characteristics in learning environment otTers many advantages. unfortunately study on this aspect in relation to serious game is still limited. To address these limitations. tour objectives were identified: to identify and analyze extsting serious game design models. to develop a model for culturally-enhanced senous game. to customize a serious game which conforms to the model and finally to evaluate the usability and effectiveness of the customized serious game.